Diagnosing Medial Ankle Instability with Gravity Stress, Weight-Bearing, and External Rotation Stress Ultrasonography: A Cadaveric Study. Issue 1 (January 2022) - Saengsin, Jirawat; Sornsakrin, Pongpanot; Sato, Go; Lubberts, Bart; Waryasz, Gregory R.; Guss, Daniel; DiGiovanni, Christopher W.
Category: Ankle; Trauma Introduction/Purpose: Destabilizing injuries to the deltoid ligament have historically relied on radiographic stress examination for diagnosis, with a focus on medial clear space (MCS) widening. Increasingly, Portable ultrasound (P-US) has increasingly been used in the clinical setting, allowing dynamic and non-invasive evaluation at the point of care. This study aims to determine whether the P-US assisted MCS evaluation during the gravity stress (GST), weight-bearing, and external rotation stress test can detect medial side instability in supination-external rotation (SER) type ankle injuries with sequential disruption of the anterior inferior tibiofibular ligament (AITFL) (stage I), the fibula (Weber B fracture) (stage II), the posterior inferior tibiofibular ligament (PITFL) (stage III), the superficial deltoid ligament (stage IVa) and the deep deltoid ligament (stage IVb). Methods: Ten fresh-frozen cadaveric specimens were used. Medial ankle instability was assessed by the P-US. The assessment was performed with all structures intact and later with sequential transection of the AITFL, Weber-B fibular fracture, the PITFL, the superficial and deep deltoid ligament. In all scenarios, three loading conditions were considered, including the GST, the external rotation stress test (45N), and the simulated weight-bearing (750N). The P-US measurement of the MCS was assessed at the anteromedial aspect and inferomedial aspect of the ankle joint. Three different MCS distances were measured, as demonstrated in Figure 1. To investigate the correlation between the P-US measurements and the staging of SER ankle injuries, a Spearman rank correlation was used. To detect a difference in MCS distances between each injured stage and the intact stage for each stress test, a Wilcoxon signed-rank test was used. P-values were adjusted for multiple comparisons using the Holm- Bonferroni method. Results: MCS values measured with the P-US increased as the SER ankle injury stage progressed. The Spearman's rank correlation coefficient ranged from 0.43 to 0.90 (p-values <0.001), which represent moderate to strong positive correlations between the ultrasonographic MCS measurements, and the sequentially created supination-external rotation ankle injury model. All MCS values measured with the P-US during; 1) the GST in neutral ankle position, 2) the GST in plantarflexed ankle position, 3) weight-bearing, and 4) the external rotation stress test, were significantly different between intact stage vs. stage IVb (p ranged from 0.02-0.03). When compared between SER ankle injury stage IVa vs. IVb, the P-US MCS values measured in SER stage IVb were significantly larger (p ranged from 0.005-0.03). Inter-rater (0.97; 95% confidence interval: 0.96-0.98) and intra-rater reliability (0.95; 95% confidence interval: 0.94-0.96) for the P-US MCS measurements were all substantial. Conclusion: Portable ultrasonography is a feasible tool for diagnosing medial ankle instability in SER ankle injury. The MCS measurements assessed with P-US during the GST, weight-bearing, and the external rotation stress test well correlated with the SER ankle injury staging. Besides, the P-US method is capable of differentiating the SER ankle injury stage IVb from the intact stage, as well as differentiating the stable SER ankle injury stage from the unstable stage. Therefore, the P-US can be a valuable diagnostic tool at the point of care due to its ability to dynamically evaluate suspect medial ankle instability in SER type injury.